2002
DOI: 10.1084/jem.20021229
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacteria Target DC-SIGN to Suppress Dendritic Cell Function

Abstract: Mycobacterium tuberculosis represents a world-wide health risk and immunosuppression is a particular problem in M. tuberculosis infections. Although macrophages are primarily infected, dendritic cells (DCs) are important in inducing cellular immune responses against M. tuberculosis. We hypothesized that DCs represent a target for M. tuberculosis and that the observed immuno-suppression results from modulation of DC functions. We demonstrate that the DC-specific C-type lectin DC-SIGN is an important receptor on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
870
7
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 950 publications
(910 citation statements)
references
References 41 publications
25
870
7
8
Order By: Relevance
“…Interestingly, blocking of the interaction between DC and T cells with an anti-DC-SIGN antibody influences allostimulatory properties in T cells [1]. Several recent studies have demonstrated that cross-talk between C-type lectins and TLR can occur [14,32,33], suggesting that simultaneous interaction of pathogens with both receptors can modulate the response by DC. In this context, a recent study indicates that activation of DC by HPV L1-VLP is MyD88 dependent [34].…”
Section: Blocking the Interaction Of L1-vlp With Dc-sign Inhibits Vlpmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, blocking of the interaction between DC and T cells with an anti-DC-SIGN antibody influences allostimulatory properties in T cells [1]. Several recent studies have demonstrated that cross-talk between C-type lectins and TLR can occur [14,32,33], suggesting that simultaneous interaction of pathogens with both receptors can modulate the response by DC. In this context, a recent study indicates that activation of DC by HPV L1-VLP is MyD88 dependent [34].…”
Section: Blocking the Interaction Of L1-vlp With Dc-sign Inhibits Vlpmentioning
confidence: 99%
“…In addition to HIV, DC-SIGN was recently shown to bind a variety of microorganisms such as CMV [4], Ebola virus [5], Dengue virus [6], hepatitis C virus [7,8], simian immunodeficiency virus [9], Leishmania [10], Candida albicans [11], Mycobacterium [12][13][14] and Schistosoma [15]. Some pathogens subvert DC functions to escape immune surveillance [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that DC interact with yeasts essentially by the mannose-binding receptors CD206 [22,31] 32,[34][35][36][37] and TLR2 [32,38,39]. Therefore, we analyzed Candida uptake in the presence of mannan, which binds both CD206 and DC-SIGN [40,41] and interferes with particle internalization by these receptors [42], or laminarin, a specific dectin-1 inhibitor [27,35,40,41,43]. Fig.…”
mentioning
confidence: 99%
“…[81] and [82] Most recently, Schlesinger and Torrelles have demonstrated that M. tuberculosis clinical isolates vary in their degree of surface mannosylation and they suggest these differences may have great impact on the outcome of the disease.78 There is direct evidence manLAM affects DC maturation and function [79], [83] and [84] and the same antigen either as a cell wall component of M. tuberculosis or as a free antigen, drives DCs into IL-10 production. [76], [85], [86], [87], [88] The role of cell death in the immune response to M. tuberculosis M. tuberculosis is an intracellular pathogen and its survival within the host requires living cells. Cell suicide is an important innate defence against intracellular pathogens.…”
Section: Role Of Mycobacterial Antigens In Persistence Of M Tuberculmentioning
confidence: 99%